Playing with your Brain: Brain-Computer Interfaces and Games - Nijholt, Anton; Tan, Desney (Organizing paper for Brainplay Workshop at Advances in Computer Entertainment 2007, 2007)
In this workshop we investigate a possible role of brain-computer interaction in computer games and entertainment computing. The assumption is that brain activity, whether it is consciously controlled and directed by the user or just recorded in order to obtain information about the user’s affective state, should be modeled in order to provide appropriate feedback and a context where brain activity information is one of the multi-modal interaction modalities that is provided to the user.